ANALISIS KEMAMPUAN KONEKSI MATEMATIS SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN CORE (CONNECTING, ORGANIZING, REFLECTING, EXTENDING) - Agustianti, Rifka; Amelia, Risma (IKIP Siliwangi, 2018)
This study aims to analyze the ability of mathematical connections of vocational students. The research population is all students of class X SMK in one of School Cimahi City. The sample taken is one class X in the private SMK as the experimental class. The research method used in this study is quasi-experimental method. Instruments in this study is a set of description tests to determine the ability of students' mathematical connections. Based on result of data analysis, it can be concluded that students' mathematical ability with CORE learning model (Connecting, Organizing, Reflecting, Extending) has high category with 5% significance level.